Proceedings of the 2008 Symposium on Eye Tracking Research &Amp; Applications - ETRA '08 2008
DOI: 10.1145/1344471.1344501
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary pupil size change as control in eyes only interaction

Abstract: We investigate consciously controlled pupil size as an input modality. Pupil size is affected by various processes, e.g., physical activation, strong emotional experiences and cognitive effort. Our hypothesis is that given continuous feedback, users can learn to control pupil size via physical and psychological self-regulation. We test it by measuring the magnitude of self evoked pupil size changes following seven different instructions, while providing real time graphical feedback on pupil size. Results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…A less known phenomenon is that pupil size also varies in response to different levels of cognitive engagement and effort [3] and in response to the interest value of stimuli [4]. In addition, recent studies have suggested that pupil size can be used to measure the effects of emotional feedback [5] and as an input modality used to control computer games [6].…”
Section: Introductionmentioning
confidence: 99%
“…A less known phenomenon is that pupil size also varies in response to different levels of cognitive engagement and effort [3] and in response to the interest value of stimuli [4]. In addition, recent studies have suggested that pupil size can be used to measure the effects of emotional feedback [5] and as an input modality used to control computer games [6].…”
Section: Introductionmentioning
confidence: 99%
“…This is what is used for all IREX analyses. 22 The default threshold is that computed using all OPS vs. OPS and OPS vs. ICE comparisons of uncompressed KIND 1 images. 23 For example, consider an enrollment process that includes capture of three images of an eye.…”
Section: The Bath Datasetmentioning
confidence: 99%
“…Drugs that cause pupillary constriction are known as miotics. Persons can be trained to vary the size of their pupils [22].…”
Section: Dilation Of the Irismentioning
confidence: 99%
“…We have also established through formal user tests that it is possible for non-expert users to achieve control of their pupil size in a controlled environment [2]. The level of control seems to be related to the type of indirect activation used to manipulate pupil size: positive activation performs well, whereas self-inflicted pain and negative emotions produce big pupil variations, but nevertheless fail to work in a regular enough fashion to serve as a control mechanism.…”
Section: Testing and Iteratingmentioning
confidence: 99%
“…Subjects were also given instructions on methods which allow indirect manipulation of pupil size, such as positive thoughts and physical activation. For details on the test procedure and results, refer to [2].…”
Section: Testing and Iteratingmentioning
confidence: 99%